Developing A Community-Based Rehabilitation Programs in Elderly Nursing Home: A Brief Descriptive Analysis - Harini, Melinda; Dosmaria, Dosmaria; Herry, Herry; Emilda, Lisa; Herman, Listyani; Nelfidayani, Nelfidayani; Mahardini, Putu K; Hantogo, Shynta D; Meiliana, Widya; Johnson, Ikhsan; Peggy, Peggy; Aries, Wanarani; Kusumaningsih, Widjajalaksmi; Wahyuni, Luh K (ASEAN Journal of Community Engagement, 2021)
The need for rehabilitation services in nursing homes (NH) for the elderly is increasing each year, and this need is fulfilled both with ordinary clinical rehabilitation center visits, as well as community-based rehabilitation (CBR) inside the facility. However, a proper situation analysis is needed to establish a well-delivered CBR program in the NH, a niche to be fulfilled in this study. This study used a descriptive measurement and cross-sectional design to target the elderly who are living in the NHs. Consecutive sampling was done in the largest NH in Jakarta, in Cipayung District. Participants who were dependently ambulated were assessed in the NH clinic, whereas the independent ones were assessed in their room. Nutritional status and blood pressure measurement was done in the first visit, whereas psychiatric and activity of daily living (ADL) were done in the second visit. In the first visit, 32 (20%) participants were undernourished, whereas 25 (83%) participants have a psychiatric disorder in the second visit. More than half of the participants were also dependent on their ADL (n: 17; 57%). Malnourishment, mental illness, and higher dependency were found in subjects, which affect the conducted CBR programs. An inter-professional team (including a nutritionist, public health expertise, physiatrist, and psychiatrist) may be needed to conduct a well-established CBR program, as well as further study to find magnitudes of each aspect.